2008
DOI: 10.3201/eid1411.080589
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Diagnosis of Bacterial Infections

Abstract: To test the ability of high-throughput DNA sequencing to detect bacterial pathogens, we used it on DNA from a patient's feces during and after diarrheal illness. Sequences showing best matches for Campylobacter jejuni were detected only in the illness sample. Various bacteria may be detectable with this metagenomic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 15 publications
0
71
1
1
Order By: Relevance
“…Anecdotal data have shown that spiral or curved bacteria are sometimes observed on stool smears while Campylobacter growth does not occur. In a recent study, DNA sequences of the Campylobacter genome were detected by a metagenomic analysis, while the standard culture methods were negative (5). In a pilot study using real-time PCR as a diagnostic tool, we also detected more campylobacters than with culture, but without being able to confirm that true positives were detected, since, at that time, we did not use multiple detection methods to establish positivity when culture was negative.…”
mentioning
confidence: 89%
“…Anecdotal data have shown that spiral or curved bacteria are sometimes observed on stool smears while Campylobacter growth does not occur. In a recent study, DNA sequences of the Campylobacter genome were detected by a metagenomic analysis, while the standard culture methods were negative (5). In a pilot study using real-time PCR as a diagnostic tool, we also detected more campylobacters than with culture, but without being able to confirm that true positives were detected, since, at that time, we did not use multiple detection methods to establish positivity when culture was negative.…”
mentioning
confidence: 89%
“…More detailed investigations of the whole pathogen communities infecting these bank voles are now possible from the development of new generation sequencing technologies and metagenomic analyses. These approaches have yet allowed to describe microbial communities and to explore their interactions in different hosts' organs or environments (Nakamura et al 2008;Carpi et al, 2011;Cheval et al, 2011). In the future, the integration of such information in the analysis of PUUV epidemiology will provide a better understanding of the impacts of co-infection on the evolution of tolerance to PUUV in bank voles.…”
Section: Perspectivesmentioning
confidence: 99%
“…Furthermore, selective media are commonly used, and the antibiotics incorporated may inhibit certain Campylobacter strains (Bessede et al, 2011). In a recent study, DNA sequences of the Campylobacter genome were detected by a metagenomic analysis, while the standard culture methods were negative (Bessede et al, 2011;Nakamura et al, 2008;Wang et al, 2002;Casademont et al, 2000).…”
mentioning
confidence: 99%